2002
DOI: 10.1002/fld.260
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of laminar flow and heat transfer over banks of staggered cylinders

Abstract: SUMMARYA study is conducted to investigate forced convective ow and heat transfer over a bank of staggered cylinders. Using a novel numerical formulation based on a non-orthogonal collocated grid in a physical plane, the e ects of Reynolds number and cylinder spacing on the ow and heat transfer behaviour are systematically studied. It is observed that both the Reynolds number and cylinder spacing in uence the recirculatory vortex formation and growth in the region between the cylinders; in turn, the rates of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Examination of the two arrangements using e ¼ 0:84 and e ¼ 0:91 revealed that the velocity gradients increase when the porosity decreases, which agrees with the information presented previously in Ref. [44]. For the sake of brevity, contours for the staggered and in-line arrangements using e ¼ 0:91 are not illustrated.…”
Section: Methodssupporting
confidence: 81%
“…Examination of the two arrangements using e ¼ 0:84 and e ¼ 0:91 revealed that the velocity gradients increase when the porosity decreases, which agrees with the information presented previously in Ref. [44]. For the sake of brevity, contours for the staggered and in-line arrangements using e ¼ 0:91 are not illustrated.…”
Section: Methodssupporting
confidence: 81%
“…et al [16]. Experiments preformed by Kosar et al [11] on micro circular pillar structures have no good agreement with that of conventional macro correlations.…”
Section: Resultsmentioning
confidence: 95%
“…The role of finite Reynolds number flow and the deviation due to non-linearities from the original Darcy's law have been extensively discussed in the literature. There are much less numerical works on heat transfer over banks of rods in low Reynolds number cross-flow [11][12][13][14][15][16]. In the context of porous media, one of the issues is that of local thermal equilibrium of the fluid and the solid matrix constituting the porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is much more complex than the isothermal one, since heat transfer not only depends on the porosity and the Reynolds number, but also on the Prandtl number and on the thermal conditions on the solid surfaces. The range of parameters and boundary conditions found in [11][12][13][14][15][16] are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%